A Case of Bilateral Acute Inferior Limb Ischemia in a Patient With Ulcerative Colitis. Issue 13 (March 2020) - Kanazawa, Mimari; Sugaya, Takeshi; Takahashi, Fumiaki; Takenaka, Kazuhiro; Tsuchida, Kouhei; Tominaga, Keiichi; Majima, Yuichi; Iijima, Makoto; Goda, Kenichi; Irisawa, Atsushi
A patient was diagnosed with ulcerative colitis (UC) in 2010. In March 2015, she had abdominal pain, diarrhea, bloody stool, and UC has relapsed. In June 2015, pain and sensory disturbance of both lower limbs appeared. Blood flow at the distal femoral artery was not confirmed with magnetic resonance angiography, and it was diagnosed as bilateral acute inferior limb ischemia. Arterial thrombolectomy with Fogarty's balloon catheter was performed and blood flow was improved. The severity of UC was moderate with Mayo score 8. Thrombosis is considered to be a complication with a high incidence in inflammatory bowel disease. Reports of arterial thrombosis are very rare. It is important to evaluate the risk of bleeding and thrombosis in active or severe cases in UC and need to do thrombotic prophylactic treatment simultaneously with UC treatment.